COASTAL PLANNING AND THE EVALUATION OF COASTAL STRUCTURES IN TERMS OF SUSTAINABILITY - (:unkn) unknown (ISEC PRESS, 2016)
Coasts are cross-sections of the water and land environments, for thousands of years they formed under the factors of climate, geological, geomorphological, topographic and hydraulic and it has reached a natural balance. But increasingly this natural balance is disrupted due to human impact. Coasts, with their strategic position, are a wealth of resources for people with endless possibilities and mild climate. Therefore, coasts continuously have remained under great pressure just because of residential, transportation, energy, economy and tourism. These pressures can be minimized by applying the principles of science and engineering with a rational urban planning. It will be held after an urban planning at the macro level, as a part of that plan, it should be considered in the design of optimal engineering structures. Therefore, the structure of the planning and design engineering for optimal site selection should be done and compatible structures integrated with topography and bathymetry such as coastal hydrodynamics should be designed. In this paper, after briefly the occurrence and type of coasts, the strategic importance of coastal will be highlighted and coastal planning and engineering structures in Turkey will be examined in terms of sustainability by demonstrating some examples and solutions will be proposed for encountered problems.
Keywords: Urban planning; Natural balance; Shoreline protection; Land use; Zoning